Analysis Of The Quality Of Rejected Layer Chicken Meatballs With The Addition Of Seaweed As A Bottle Ingredient - Azhary, Indry; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
Eucheuma Cottonii type seaweed has good properties as a thickening agent because it has the ability to form a gel, so it can be used as an alternative natural additive in the manufacture of rejected layer chicken meatballs. This study aimed to analyze the quality of rejected layer chicken meatballs with the addition of seaweed as a thickening agent as much as 0%, 15%, 30% and 45% in organoleptic tests on shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design (CRD) method with three repetitions. The data collection technique was carried out by giving research questionnaires to 3 expert panelists who were lecturers of Catering at the State University of Padang. Data were analyzed using ANOVA, if Fcount Ftable then continued with Duncan's test. The results showed that there was a significant effect on the quality of the shape and texture of the rejected layer meatballs produced from the addition of seaweed. The more seaweed used, the more chewy the texture of the meatballs will be. The results of the quality test of laying hens that were rejected with the addition of seaweed were the best in the fourth treatment (X3) with the addition of 45% seaweed. Keywords: Rejected layer chicken, Meatballs, Seaweed, Quality